2023
DOI: 10.1177/13623613231182801
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile health technology to assess childhood autism in low-resource community settings in India: An innovation to address the detection gap

Abstract: A diagnosis of autism typically depends on clinical assessments by highly trained professionals. This high resource demand poses a challenge in low-resource settings. Digital assessment of neurodevelopmental symptoms by non-specialists provides a potential avenue to address this challenge. This cross-sectional case-control field study establishes proof of principle for such a digital assessment. We developed and tested an app, START, that can be administered by non-specialists to assess autism phenotypic domai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…A total of 4 studies involving 4 unique apps were included in the review ( Figure 2 ), of which 1 (Canvas Dx [ 16 ]) was an FDA-cleared commercial product and 3 (Guess What? [ 17 ], START [ 18 ], and SenseToKnow [ 19 ]) were research apps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4 studies involving 4 unique apps were included in the review ( Figure 2 ), of which 1 (Canvas Dx [ 16 ]) was an FDA-cleared commercial product and 3 (Guess What? [ 17 ], START [ 18 ], and SenseToKnow [ 19 ]) were research apps.…”
Section: Resultsmentioning
confidence: 99%
“…Our work also outlined exciting trends toward the development of mobile-first digital technologies. It has been shown that while individuals in underserved communities often do not have access to desktop computers or laptops, the availability of mobile phones is typically higher [ 18 ]. Therefore, developing mobile-first tools could help ensure health equity in communities where conditions like autism suffer from greater diagnostic delays [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The STREAM platform’s content and design are built upon three established and complementary child development measurement tools, previously developed, field-tested, and validated by the team for use in low-resource settings: the Malawi Developmental Assessment tool (MDAT; Gladstone et al, 2010), DEvelopmental assessment on an E-Platform (DEEP; Bhavnani et al, 2019), and the Screening Tool for Autism Risk using Technology (START; Dubey et al, 2024). The integration of these tools within STREAM was piloted on N=15 children in India and N=17 in Malawi to assess the need for cultural adaptation and to inform the development of Standard Operating Protocols (SOPs) and assessor training procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility and acceptability to stakeholders of the three established tools included within the STREAM tablet-based platform have been assessed previously (Gladstone et al, 2010;Dubey et al, 2024;Bhavnani et al, 2019). Local stakeholders within the recruitment catchment areas were consulted before commencing STREAM data collection.…”
Section: Patient and Public Involvementmentioning
confidence: 99%
See 1 more Smart Citation